Construction Projects Duration Derivatives, Correlations Analysis Justified by Frequency Count and Questionnaire - Zaid B. OWAIS (SEA: Practical Application of Science)
The performance of construction projects is often measured by the triad of cost, quality, and time. However, many projects fail to meet these criteria, leading to significant cost overruns and delays. This research investigates the micro-level factors contributing to time and cost overruns in construction projects. Utilising a mixed-methods approach, the study combines qualitative data from a comprehensive survey of field professionals and quantitative data from a detailed case study of a hospital construction project in northern Jordan. The findings reveal that changes during the project lifecycle, particularly those stemming from requirement modifications and miscommunication, are the primary drivers of delays. While the number of workforce personnel influences activity duration, its impact is secondary to that of changes. The study underscores the critical need for effective change management and communication strategies to mitigate delays and enhance project performance. These insights offer valuable contributions to the construction industry, providing practical recommendations for improving project outcomes through better management practices. The research emphasizes the importance of workforce quality, skill, and contractual arrangements, thereby presenting a comprehensive analysis of the factors affecting construction project success.